Analisis Aktivitas Belajar Siswa dalam Pembelajaran IPAS Kurikulum Merdeka Kelas 4 SDN 1 Tiudan Tulungagung - Izza Mawadati; Rohmatus Syafi'ah; Ria Fajrin Rizqy Ana (Jurnal Simki Postgraduate, 2023)
Student learning activity is a process of student learning activities that causes changes in behavior or skills. Learning activities are very important for students, because they can provide opportunities for students to be in contact with the object being studied as widely as possible. The use of learning methods also affects student learning activities. This study aims to describe student learning activities in the Science subject of the independent curriculum for grade 4 at SDN 1 Tiudan. This type of research is descriptive qualitative. The subjects of this research were students of class IV. The object is the Analysis of Class 4 Student Learning Activities at SDN 1 Tiudan in Independent Curriculum Science Learning. The key informants were 34 students of class IV and 1 supporting informant, namely the homeroom teacher of class IV. Data collection techniques used observation, questionnaires, and documentation. Data analysis techniques using data reduction, data presentation, and drawing conclusions. Data from research on student learning activities in grade 4 science learning at SDN 1 Tiudan obtained a percentage of 76.4%. Where this figure belongs to the good category. This can be seen in the fourth grade students at SDN 1 Tiudan who have carried out aspects of learning activities, namely visual activities, mental activities, listening activities, oral activities, physical activities, and emotional activities.